Analysis of Covid-19 Pandemic and Migration to Distance Learning and Digital Education in Public Tertiary Institutions in Abia State - Dickson, Solomon Makasda; Enock, Sarah Banku (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The study was conducted to examine the analysis of Covid-19 pandemic and migration to distance learning and digital education in public higher institution in Abia State. Covid-19 pandemic era is simply a period everything and sectors of the economy was paralyzed and all activities were halted. It implies that teaching activities and learning activities in traditional classrooms were affected. The aimed of this study was to determine the extent to which public higher institutions in Abia to migrate to digital education in the covid-19 pandemic era. This objectives was to examine how equal education opportunities and curriculum implementation during the Covid-19 pandemic era in public tertiary institutions in Abia State. Two research questions were raised and answered for the study. Two research hypotheses were formulated and tested at .05 level of significance. Descriptive survey research design was adopted while structured questionnaire were used for data collection. The population of the study consisted of all the public tertiary institutions in Abia State while the sample random sampling technique was in the study. The Statistical for Social Science (SPSS) was used as the statistics for data analysis which help in realizing the objectives of the study. From the findings of the study, both tertiary institution and Government as well as the lecturers are instrument for improving migration to digital education in higher institutions in Abia State.